The Concept of Nasionalisme in Indonesian Stand-up Comedy by Pandji Pragiwaksono - Sihombing, Lambok Hermanto (Graduate School of Institut Seni Indonesia Yogyakarta, 2025)
The integration of cultural beliefs with nationalism is one of the most intriguing aspects of the development of national identity and unity. Pandji Pragiwaksono, an Indonesian stand-up comic, consistently integrates shared cultural values and representations into his performances to contribute to understanding Indonesian society towards nationalism issue. In his stand-up comedy performance, he emphasizes the importance of nurturing a sense of nationalism toward Indonesia as a nation. This article aims to investigate how Pandji incorporates cultural assumptions and representations into his performances, Nasional.is.me. This study used Stuart Hall's Representation theory as the data and Relevance theory for analysis to examine how he integrates shared cultural knowledge into his performances. In the performance, he engages in creative interactions with cultural beliefs and representations to mediate and negotiate the principle of nationalism. Konsep Nasionalisme dalam Komedi Stand-up Indonesia oleh Pandji Pragiwaksono Abstrak Integrasi antara keyakinan budaya dan nasionalisme adalah salah satu aspek yang paling menarik dalam pengembangan identitas dan kesatuan nasional. Pandji Pragiwaksono, seorang komika stand-up Indonesia, secara konsisten mengintegrasikan nilai-nilai dan representasi budaya bersama ke dalam pertunjukannya untuk berkontribusi dalam memahami masyarakat Indonesia terhadap isu nasionalisme. Dalam pertunjukan stand-up comedy-nya, ia menekankan pentingnya memupuk rasa nasionalisme terhadap Indonesia sebagai sebuah bangsa. Penulisan ini bertujuan untuk mengetahui bagaimana Pandji memasukkan sudut pandang dan representasi budaya ke dalam pertunjukannya, Nasional.is.me. Penelitian ini menggunakan teori Representasi dari Stuart Hall sebagai data dan teori Relevansi untuk menganalisis bagaimana ia mengintegrasikan pengetahuan budaya yang dimiliki ke dalam pertunjukannya. Dalam pertunjukannya, ia terlibat dalam interaksi kreatif dengan kepercayaan dan representasi budaya untuk memediasi dan menegosiasikan prinsip nasionalisme.